Image-Based Assessment of Drought Response in Grapevines - Briglia, Nunzio; Williams, Kevin; Wu, Dan; Li, Yaochen; Tao, Sha; Corke, Fiona; Montanaro, Giuseppe; Petrozza, Angelo; Amato, Davide; Cellini, Francesco; Doonan, John H.; Yang, Wanneng; et al. (Frontiers in Plant Science, 2020)
Introduction Many plants can modify their leaf profile rapidly in response to environmental stress. Image-based data are increasingly used to retrieve reliable information on plant water status in a non-contact manner that has the potential to be scaled to high-throughput and repeated through time. This paper examined the variation of leaf angle as measured by both 3D images and goniometer in progressively drought stressed grapevine. Grapevines, grown in pots, were subjected to a 21-day period of drought stress receiving 100% (CTRL), 60% (IRR60%) and 30% (IRR30%) of maximum soil available water capacity. Leaf angle was (i) measured manually (goniometer) and (ii) computed by a 3D reconstruction method (multi-view stereo and structure from motion). Stomatal conductance, leaf water potential, fluorescence (Fv/Fm), leaf area and 2D RGB data were simultaneously collected during drought imposition. Throughout the experiment values of leaf water potential ranged from -0.4 (CTRL) to -1.1 MPa (IRR30%) and it linearly influenced the leaf angle when measured manually (R2=0.86) and with 3D image (R2=0.73). Drought was negatively related to stomatal conductance and leaf area growth particularly in IRR30% while photosynthetic parameters (i.e. Fv/Fm) were not impaired by water restriction. A model for leaf area estimation based on the number of pixel of 2D RGB images developed at a different phenotyping robotized platform in a closely related experiment was successfully employed (R2=0.78). At the end of the experiment, top view 2D RGB images showed a approx. 50% reduction of greener fraction (GGF) in CTRL and IRR60% vines compared to initial values, while GGF in IRR30% increased by approx. 20%. The influence of juvenile dichromatism of leaf occurring for specific varieties on the determination of colour-based indexes has been discussed.